2010
DOI: 10.1128/jcm.00022-10
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Determinants of Staphylococcus aureus Carriage in Infancy: the Generation R Study

Abstract: We recently discovered that mistakes were made during the development of the database that was fundamental to the research we presented in the article identified above. Numerical mistakes were inadvertently included in Table 1; also, the statistical analyses were performed with the wrong data. The numbers of individuals included in the gender data in Table 1 were wrong. As a consequence, all of the data for the other parameters listed in that table were miscalculated. The corrected table, in which many of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 0 publications
6
32
2
2
Order By: Relevance
“…Additionally, they are likely to be exposed to colonising S. aureus of older persons who carry them on regular basis. However, our finding is similar to that of Lebon and colleagues recent study on the dynamics of S. aureus nasal carriage, its human and microbial determinants in the first year of life (Lebon et al, 2008). The workers documented a significant decrease in the prevalence of S. aureus carriage in children in the first year of life and suggested that it may be attributed to bacterial interference with other organisms present in the nasopharynges of children.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, they are likely to be exposed to colonising S. aureus of older persons who carry them on regular basis. However, our finding is similar to that of Lebon and colleagues recent study on the dynamics of S. aureus nasal carriage, its human and microbial determinants in the first year of life (Lebon et al, 2008). The workers documented a significant decrease in the prevalence of S. aureus carriage in children in the first year of life and suggested that it may be attributed to bacterial interference with other organisms present in the nasopharynges of children.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were demonstrated by Allaker et al [24] for S. hyicus in gnotobiotic piglets. Bacterial interference between S. aureus and Streptococcus pneumoniae in children may explain why children are less likely to be persistent carriers of S. aureus in early infancy [25,26]. Failure of the nasal-gastrointestinal inoculation method could also be related to inherent variability in host susceptibility to MRSA colonization, since our experiment was conducted on a small number of genetically related animals.…”
Section: Discussionmentioning
confidence: 99%
“…Research nurses obtained a nasal swab for S. aureus isolation from each infant at each visit, whenever possible. The methods of nasal sampling and identification of S. aureus were as described previously [5]. Serum samples were collected from cord blood and through venipuncture at 6 months, 14 months and 24 months whenever possible.…”
Section: Study Populationmentioning
confidence: 99%
“…During the first 2 months of life, the prevalence of colonization is 40-50%. Then, the prevalence rapidly decreases to approximately 20% by 6 months and to 10% by 14 months [5,6]. How nasal carriage is established and maintained is still largely unknown [2,7], although the involvement of bacterial components such as teichoic acid, catalase, hydroperoxide reductase, iron-responsive surface determinant A (IsdA), S. aureus surface protein G and clumping factor B (ClfB) has been demonstrated [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%